If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2c + -1) = (c + -5) Reorder the terms: (-1 + 2c) = (c + -5) Remove parenthesis around (-1 + 2c) -1 + 2c = (c + -5) Reorder the terms: -1 + 2c = (-5 + c) Remove parenthesis around (-5 + c) -1 + 2c = -5 + c Solving -1 + 2c = -5 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. -1 + 2c + -1c = -5 + c + -1c Combine like terms: 2c + -1c = 1c -1 + 1c = -5 + c + -1c Combine like terms: c + -1c = 0 -1 + 1c = -5 + 0 -1 + 1c = -5 Add '1' to each side of the equation. -1 + 1 + 1c = -5 + 1 Combine like terms: -1 + 1 = 0 0 + 1c = -5 + 1 1c = -5 + 1 Combine like terms: -5 + 1 = -4 1c = -4 Divide each side by '1'. c = -4 Simplifying c = -4
| 12y-18/2 | | 16x-3=68+13+4x | | 2x+4x+2x+1+5x-6=60 | | r/s=25 | | 9x+1=9(1)+2 | | (37b-8)-9(4b+4)=-2 | | 96.8639/883.3525= | | 1-0.4p=2 | | 3x-6=-7x-6 | | 1x+16+56=90 | | (7+y)(5y+3)= | | 11x+35+35=180 | | 3p-42=31 | | 1-0.4=2 | | 18x-4+4x=172 | | 8w+12-6w=5(w+3)-2w | | a^2-16a+63=0 | | .5x+4=-6 | | -1+4/25=-1 | | 4x*2c-4+4c=0 | | t(p)=(ln(p/25))/.12 | | 2z+8-9=-30.5 | | m+3-(2)=7 | | .6n+4=18 | | 8x=x-2 | | (-9x-3).2/3 | | r^2-16r+15=0 | | 34x+3+96+59x+75=360 | | 9k+3=12k | | 130+48+14x=360 | | 2w+7=16 | | 42j+19j-18=28 |